1997
DOI: 10.1016/s0266-7681(97)80417-2
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Aneurysm of a Common Digital Artery

Abstract: We describe a false aneurysm of a common digital artery. Diagnosis and choice of treatment were largely determined by ultrasonography which proved to be a reliable and easy to use diagnostic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…1,2,7,9,10 We believe that even without doubt about distal perfusion, restoration of the normal blood flow is always preferable, especially in children.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,7,9,10 We believe that even without doubt about distal perfusion, restoration of the normal blood flow is always preferable, especially in children.…”
Section: Discussionmentioning
confidence: 99%
“…We found that a preoperative ultrasound scan provided simple, non-invasive confirmation of the suspected diagnosis, and although others have reported success using angiography or magnetic resonance [2,7,8], ultrasound does not need intravenous contrast agents, is patient-friendly, and its near field resolution is superior to that of the other techniques in diagnosing small lesions in the hand. Plain radiographs have been helpful only in cases in which a longstanding aneurysm has caused erosive changes to adjacent bone [9].…”
Section: Discussionmentioning
confidence: 75%
“…An appreciable number of previous case reports have described the mass as being non-pulsatile [4], probably because of the organising thrombus within the aneurysm, and in these cases the mass may be mistaken for an epidermoid cyst, a foreign-body granuloma, a neuroma, or an abscess. The correct diagnosis is usually made intraoperatively or on histological examination [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of these lesions can be a matter of debate. Although conservative methods for the treatment of small, uncomplicated and fully thrombosed false aneurysms such as observation and compression bandage have been described [7][8][9], this could be dangerous due to the risk of distal embolization with subsequent occlusion of the run-off arteries. Therefore, we consider surgery the treatment of choice for the superficial palmar arch false aneurysms.…”
Section: Discussionmentioning
confidence: 99%